Особенности онтогенеза и анатомического строения пластинки листа Physalis pubescens L. (Solanaceae Juss.) на разных фазах его развития в условиях Донбасса - Горлачева, З.С. (Промышленная ботаника, 2003)
This study was conducted to give the detailed characteristics of the stages of ontogenetic development and peculiarities of the anatomic structure of seed-lobes and first leaves. It was noted that such age-states as immature and virgin ones had no distinct limits, virgin state being very short and senile period being not distinguishable, as the plant perished from the late durative frosts when blossoming and bearing fruits. Studies of the anatomic structure showed that such features as the number of stomas and cell size was labile, and the structure of mesophyll was relatively permanent notwithanding the development phase and leaf order. The optimum terms of sowing seeds into the ground have been determined.